Crystal structure of CspA, the major cold shock protein of Escherichia coli. - Schindelin, H (1994)
The major cold shock protein of Escherichia coli, CspA, produced upon a rapid downshift in growth temperature, is involved in the transcriptional regulation of at least two genes. The protein shares high homology with the nucleic acid-binding domain of the Y-box factors, a family of eukaryotic proteins involved in transcriptional and translational regulation. The crystal structure of CspA has been determined at 2-A resolution and refined to R = 0.187. CspA is composed of five antiparallel beta-strands forming a closed five-stranded beta-barrel. The three-dimensional structure of CspA is similar to that of the major cold shock protein of Bacillus subtilis, CspB, which has recently been determined at 2.45-A resolution. However, in contrast to CspB, no dimer is formed in the crystal. The surface of CspA is characteristic for a protein interacting with single-stranded nucleic acids. Due to the high homology of the bacterial cold shock proteins with the Y-box factors, E. coli CspA and B. subtilis CspB define a structural framework for the common cold shock domain.